APOPTOSIS OF NEUTROPHILS, MONOCYTES, AND LYMPHOCYTES IN THE PERIPHERAL BLOOD OF COWS DURING LACTATION - Zhelavskyi, Mykola (Polish Journal of Natural Sciences, 2024)
The immune system of animals plays an important role in the homeostasis system. This aimed at the apoptosis of immune cells of the peripheral bloodstream and milk secretions at different periods of lactation in cows. The investigation of the immune defense of cows was conducted during various lactation periods: early (3-5 days), mid (90-150 days), and late (drying off - 5-7 days; dry period - 12-20 days) periods of mammary gland function. The highest intensity of apoptosis neutrophils (P<0.01) and monocytes (P<0.01) in the mid-lactation period. The highest intensity of apoptosis is observed in phagocytic cells during the secretions colostrum period and mammary gland involution. The study of physiological constants of blood cell apoptosis will serve as a basis for developing informative methods of mastitis diagnosis in cows and implementing effective treatment measures. The findings obtained from this research are valuable for practical veterinarians and from a public health perspective.